Predictors of mortality in patients with rheumatoid arthritis in Lithuania: Data from a cohort study over 10 years - Jolanta Dadonienė; Sigita Stropuvienė; Rimantas Stukas; Algirdas Venalis; Tuulikki Sokka-Isler (Medicina, 2015)
Background and objective: Increased mortality and shorter survival among rheumatoid arthritis (RA) patients are recognized but not fully explained. This cohort study aimed to identify predictors of mortality among RA patients at a tertiary clinical setting. Materials and methods: Patients with RA were recruited during 1998–2003 and followed up until April 1, 2012, or death whichever happened first. Baseline variables included sociodemographic and disease characteristics, and comorbidities. Cox regression and hazard risk (HR) were computed to estimate risks for mortality. Results: One hundred ninety-one patients were included into the study, 186 patients were eligible for the analysis and of these 131 patients (70.4%) completed the entire period of followed-up while 55 patients (29.6%) died. The average follow up period was equivalent to 9.24 year per person. A Cox regression model identified four major factors having an impact on survival. History of a stroke at baseline was identified as a major factor (HR = 5.33; 95% CI, 2.13–13.32). Statistically significant risk factors were also age over 50 years (HR = 4.59; 95% CI, 2.04–10.30); education less than 11 years (HR = 3.3; 95% CI, 1.72–6.33) and angina pectoris (HR = 1.98; 95% CI, 1.03–3.80). Conclusions: Higher age, lower education and cardiovascular comorbidities were identified as predictors of mortality in this prospective cohort study while disease-related variables were not independent predictors of mortality.